REHABILITACJAThe importance and effectiveness of walking training in cardiac rehabilitation with special regard to patients after cardiac surgery - Kocur, Piotr; Krzywicka-Michałowska, Monika; Wilk, Małgorzata; Dylewicz, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Rehabilitation based on physical exercise should focus not only on improving the current level of physical fitness, but also on increasing patients’ awareness and forming a habit of physical activity as a form of secondary cardiovascular disease prevention. The aim of this article is to review the most current publications on this subject and point to the importance of walking training in successful cardiac rehabilitation, even for cardiac surgery patients. The authors of this article postulate the necessity of propagating simple forms of physical activity, such as walking training, as an important factor in reducing the incidence and recurrence of cardiovascular diseases as well as the resulting mortality rate.